Performances of an air thermal energy utilization system developed with fan-coil units in large-scale plastic tunnels covered with external blanket - Zong, Chengji; Xiao, Zibin; Song, Weitang; Wang, Pingzhi; Zhang, Guifang; Li, Ming (International Journal of Agricultural and Biological Engineering, 2022)
To improve the problem of low temperature at night in winter due to the lack of thermal storage in large-span plastic tunnels, an air thermal energy utilization system (ATEUS) was developed with fan-coil units to heat a large-scale plastic tunnel covered with an external blanket (LPTEB) on winter nights. The ATEUS was composed of nine fan-coil units mounted on top of the LPTEB, a water reservoir, pipes, and a water circulation pump. With the heat exchange between the air and the water flowing through the coils, the thermal energy from the air can be collected in the daytime, or the thermal energy in the water can be released into the LPTEB at night. On sunny days, the collected thermal energy from the air in the daytime (Ec) and released thermal energy at night (Er) were 0.25-0.44 MJ/m2 and 0.24-0.38 MJ/m2, respectively. Used ATEUS as a heating system, its coefficient of performance (COP), which is the ratio of the heat consumption of LPTEB to the power consumption of ATEUS, ranged from 1.6-2.1. A dynamic model was also developed to simulate the water temperature (Tw). Based on the simulation, Ec and Er on sunny days can be increased by 60%-73% and 38%-62%, respectively, by diminishing the heat loss of the water reservoir and increasing the indoor air temperature in the period of collecting thermal energy. Then, the COP can reach 2.6-3.8, and the developed ATEUS can be applied to heating the LPTEB in a way that conserves energy.Keywords: large scale plastic tunnel, air thermal energy utilization system, energy conservation, COPDOI: 10.25165/j.ijabe.20221505.6428Citation: Zong C J, Xiao Z B, Song W T, Wang P Z, Zhang G F, Li M. Performances of an air thermal energy utilization system developed with fan-coil units in large-scale plastic tunnels covered with external blanket. Int J Agric & Biol Eng, 2022; 15(5): 56–62.